Defining Global Thresholds for Serum Ferritin: A Challenging Mission in Establishing the Iron Deficiency Diagnosis in This Era of Striving for Health Equity - Rodolfo Delfini Cancado; Lauro Augusto Caetano Leite; Manuel Muñoz (Diagnostics)
Iron deficiency (ID) is a critical public health issue globally and the most prevalent cause of anemia. Iron deficiency anemia (IDA) affects approximately 1.2 billion individuals worldwide, and it is estimated that non-anemic iron deficiency (NAID) is at least twice as common as IDA. Yet, there is still uncertainty about how to diagnose it in clinical practice. The serum ferritin (SF) threshold of <15 ng/mL proposed by the World Health Organization (WHO) has been questioned over the last decade. The current SF thresholds are inappropriately low, and, therefore, a large portion of the population at the most significant risk of ID remain undiagnosed and untreated. The correlation between SF, hepcidin, and the physiological upregulation of iron absorption in healthy adults suggests that SF of <50 ng/mL indicates a more precise threshold for diagnosing ID in adults. Therefore, adopting the SF threshold <50 ng/mL would break up the perpetuation of an inequitable cycle of disadvantage for ID individuals, especially among women.